Serum Amyloid Biomarkers, Tau Protein and YKL-40 Utility in Detection, Differential Diagnosing, and Monitoring of Dementia - Wilczyńska, Karolina; Maciejczyk, Mateusz; Zalewska, Anna; Waszkiewicz, Napoleon (Frontiers in Psychiatry, 2021)
Introduction: The diagnosis and treatment of dementia is one of the greatest challenges in contemporary health care. The widespread use of dementia biomarkers would improve the quality of life of patients and reduce the economic costs of the disease. The aim of the study was to evaluate the usefulness of proteins related to the Alzheimer's disease pathogenesis - amyloid beta isoform (Aβ) and total tau protein (t-tau), as well as the quite recently discovered marker YKL-40 in the the most common types of dementia. Methods: 60 dementia (AD – Alzheimer’s disease, VaD – vascular dementia, MxD – mixed dementia) and 20 cognitively normal subjects over 60 years old were examined. Subjects with dementia of etiology different than AD or VaD and with neoplastic or chronic inflammatory diseases were excluded. Concentrations of Aβ40, Aβ42, t-tau, and YKL-40 were measured in serum using ELISA kits on admission and after 4 weeks of inpatient treatment. ANOVA and Tukey’s test or Dunn’s test were used to perform comparison tests between groups. Correlations were measured using Pearson’s coefficient. Biomarker diagnostic utility was assessed with ROC analysis. Results: YKL-40 differentiates between cognitively normal and mild dementia patients with 85% sensitivity and specificity and t-tau with 72% sensitivity and 70% specificity. YKL-40 and t-tau concentrations correlate with each other and with the severity of clinically observed cognitive decline. Conclusions: YKL-40 is a sensitive and specific biomarker of early dementia and, to a lesser extent, of dementia progression, however, many comorbidities may influence its levels. In such conditions, less specific but still reliable t-tau may serve as an alternative marker. Obtained results did not confirm the diagnostic utility of amyloid biomarkers.